1997
DOI: 10.1007/bf01844752
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of extradural haematomas: Effects of skull fractures on resorption rate

Abstract: In conservative management of extradural haematomas (EDH), several mechanisms were described to explain the resorption of the haematoma. One of these was the transfer of the clot into the epicranial space through the skull fracture. In this study, the effects of skull fracture and associated intracranial lesions in the conservative management of EDH were investigated. Skull fracture and associated intracranial lesions were found in 71.11% and 51.1% of the patients, respectively. Resorption rate was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…Since this area was filled with the venous blood of the basilar plexus dynamically, why does the blood not continue to fill the space? An epidural hematoma at the lateral calvarial region could be resolved spontaneously, because there is no venous sinus below (6,28). It is possible that initial trauma causes bleeding at the outset, from the basilar plexus, but when the hematoma creates a sufficient level of pressure, cessation of bleeding may result.…”
Section: Discussionmentioning
confidence: 99%
“…Since this area was filled with the venous blood of the basilar plexus dynamically, why does the blood not continue to fill the space? An epidural hematoma at the lateral calvarial region could be resolved spontaneously, because there is no venous sinus below (6,28). It is possible that initial trauma causes bleeding at the outset, from the basilar plexus, but when the hematoma creates a sufficient level of pressure, cessation of bleeding may result.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism for the resolution of extradural blood is the evacuation through overlying skull fractures that commonly accompany EDH. Tuncer et al [21] reported a higher rate of spontaneous resorption in patients with additional skull fracture compared to pa-…”
Section: Discussionmentioning
confidence: 99%
“…Mass effect is seen frequently [20]. Additional skull fractures were seen in 65-100% of cases with acute EDH in different series [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the past these hematoma were occasionally discovered even some weeks after the injury during the course of neurosurgery for other reason namely dural plastic surgery of ACF. Some expressed doubts concerning the need to remove EDH in patients affected by subjective disorders only and without neurological deficits [20], One of the several mechanisms to explain the resorption of the hematoma was the transfer of the clot into the epicranial space through the skull fracture [21].…”
Section: Vmentioning
confidence: 99%